Traditional farming within the Carpathian basin - pomaceous fruits - G. Tóth, M.; Szani, Zs. (International Journal of Horticultural Science, 2004)
In the Carpathian basin there are still maintained the main historical fruit varieties and traces of traditional farming. The Department of Fruit Science considered the utilisation of obsolete varieties in breeding as source of resistance to local adversities, moreover, the practice of traditional .farming using those varieties should be also explored. In the present study, the farming methods and variety structure of two substantially different growing sites are described. One is an alluvial plain along a river were an ancient form of farming based on the control of sluices. The second is practised by clearing the forest on the slopes of the central range and of the Carpathian chain. During the course of our research we succeeded to find 8 pear, 29 apple and a few quince as well as medlar varieties. Further endeavour would be the conservation of those varieties, preferably on the spot together with their growing techniques as relicts, also as aesthetic components of that particular landscape. Our committed partners in this work are the National Parks.